2013
DOI: 10.2478/s11687-013-0131-5
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of digenean parasites from three snail species, Bithynia fuchsiana (Morelet), Parafossarulus striatulus Benson and Melanoides tuberculata Müller, in North Vietnam

Abstract: 190 SummaryFor first time, 3 species of prosobranchial snails (Bithynia fuchsiana, Parafossarulus striatulus (Bithyniidae) and Melanoides tuberculata (Thiaridae)) from North Vietnam were studied for presence of the parthenitae and cercariae of Trematoda. The morphology of 12 species of larvae belonging to 8 families (Cyathocotylidae, Pleurogenidae, Lecithodendriidae, Paramphistomidae, Heterophyidae, Notocotylidae, Psilostomidae and Echinostomatidae) was described. Data on the life cycles of 3 species (Echinoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…(xiphidiocercous) [40]. Besprozvannykh et al [28] also found 5 cercariae types from P. manchouricus in North Vietnam, namely Echinochasmus japonicus (echinostome), N. intestinalis (monostome), Sphaeridiotrema monorchis (gymnocephalous), Holostephanus sp. (furcocercous), Pleurogenidae gen. sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(xiphidiocercous) [40]. Besprozvannykh et al [28] also found 5 cercariae types from P. manchouricus in North Vietnam, namely Echinochasmus japonicus (echinostome), N. intestinalis (monostome), Sphaeridiotrema monorchis (gymnocephalous), Holostephanus sp. (furcocercous), Pleurogenidae gen. sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of thiarid snails as first intermediate hosts of liver flukes has been questioned by Bui et al [26] and Nguyen et al [27], as they did not find cercariae of C. sinensis within thousands of specimens of thiarid snails collected from areas known to be highly endemic for clonorchiasis in Vietnam. In addition, Besprozvannykh et al [28] experimentally exposed fish to all cercarial types shed from M. tuberculata collected from Northern Vietnam and found no C. sinensis metacercaria. Similarly, in China, Zhang et al [12] found C. sinensis larvae within four snail species, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies reported Bithynia sp. (common in Hungarian freshwaters, but not present in fish ponds) as the first intermediate host of cyathocotylid trematodes in freshwaters ( Besprozvannykh et al, 2013 ; Erasmus, 1962 ; Serbina, 2014 ). The source of the infection in the Hungarian cyprinid fish may be non-detected infected snails in ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical fauna of digeneans is apparently much understudied and no wonder that some findings may be strikingly unlike anything previously described. Among digeneans found in freshwater gastropods of South-East Asia (Sewell 1922, Ito et al 1962, Ditrich et al 1992, Dechruksa et al 2007, Jayawardena et al 2011, Besprozvannykh et al 2013, Chontananarth and Wongsawad 2013 nothing similar to Cercaria cattieni 1 has been reported. Survey of the literature considering digenean larvae in other geographical regions and other types of environment (marine, terrestrial) produced the same result.…”
Section: Discussionmentioning
confidence: 99%